Is in-utero exposure to cannabis associated with the risk of attention deficit with or without hyperactivity disorder? A cohort study within the Quebec Pregnancy Cohort. Issue 8 (8th August 2022) - Tchuente, Vanina; Sheehy, Odile; Zhao, Jin-Ping; Gorgui, Jessica; Gomez, Yessica-Haydee; Berard, Anick
Abstract : Importance and objective: Prenatal cannabis effect on attention deficit with or without hyperactivity disorder (ADHD) remains to be determined. Our aim is to quantify the impact of in-utero exposure to cannabis on the risk of ADHD. Design: Cohort study. Setting: Questionnaires were mailed to women sampled from the Quebec Pregnancy Cohort (QPC). Data from questionnaires were then linked with their QPC (built with administrative health databases, hospital patient charts and birth certificate databases). Participants: Respondents who gave birth to a singleton live born between January 1998 and December 2003 and were continuously enrolled in the Régie de l'assurance maladie du Québec (RAMQ) medication insurance plan for at least 12 months before the first day of gestation and during pregnancy. Exposure: In-utero cannabis exposure was based on mothers' answers to the question on cannabis use during pregnancy (yes/no) and categorised as occasionally, regularly exposed and unexposed if they chose one of these categories. Outcomes: ADHD was defined by a diagnosis of ADHD through the RAMQ medical services or MedEcho databases or a prescription filled for ADHD medication through RAMQ pharmaceutical services between birth and the end of the follow-up period. Follow-up started at the birth and ended at the index date (first diagnosis or prescription filled for ADHD), child death (censoring), end of public coverage for medications (censoring) or the end of study period, which was December 2015 (censoring), whichever event came first. Results: A total of 2408 children met the inclusion criteria. Of these children, 86 (3.6%) were exposed to cannabis in-utero and 241 (10.0%) had an ADHD diagnosis or medication filled. After adjustments for potential confounders, no significant association was found between in-utero cannabis exposure (occasional (1.22 (95% CI 0.63 to 2.19)) or regular (1.22 (95% CI 0.42 to 2.79))) and the risk of ADHD in children. Conclusions: In-utero exposure to cannabis seemed to not be associated with the risk ADHD in children.